Trait-specific responses of Scots pine to irrigation on a short vs long time scale. (27th January 2015) - Feichtinger, Linda M.; Eilmann, Britta; Buchmann, Nina; Rigling, Andreas
Abstract : In xeric environments, an increase in drought is related to reduced forest productivity and to enhanced mortality. However, predictions of future forest development remain difficult as the mechanisms underlying the responses of mature trees to long-term variations in water availability are not well understood. Here, we aimed to compare the adjustments in radial growth and morphological needle and shoot traits of mature Scots pine ( Pinus sylvestris L.) growing along open water channels with those of control trees growing under naturally dry conditions at three sites in Valais, an inner-Alpine dry valley of Switzerland. The trees growing along two channels had been irrigated since germination (>70 years), whereas those along another previously drained channel had been irrigated only from 2010 to 2012, when the channel was re-established, and could thus be used to quantify the short-term effects of re-irrigation. Linear mixed models revealed that needle and shoot lengths as well as early- and late-wood basal area increments (BAIs) were most responsive to short-term and long-term irrigation. However, the magnitude of the response to the short-term irrigation exceeded that of the long-term irrigation. An extreme drought during the first half of 2011 led to an immediate decrease in the needle length, needle width, and early- and late-wood BAIs of the control trees, whereas the shoot length and needle numbers of control trees reacted with a 1-year delay to the extreme drought, as the shoots were responding to water availability of previous year's summer. Such negative responses to dry climatic conditions were even found in irrigated trees at one of our sites, which might be linked to tree growth becoming more sensitive to drought with increasing tree height and leaf area. In order to improve predictions of future forest development, long-term studies are necessary that consider lagged responses and adjustment processes of trees to changes in water availability.